Estabilidade estocástica de sistemas lineares com Saltos Markovianos e Sistemas Lineares com Saltos Semimarkovianos - Takamoto, Luana Hidemi [UNESP] (2014)
In this work, we present a study of Markov jump linear systems (MJLS) and Semi- Markov jump linear systems (S-MJLS). The MJLS are used to model systems subject to failures or abrupt changes in structure. Here, we study important results related to second moment stability of a continuous-time MJLS with infinite-time horizon. These results present necessary and sufficient conditions for stability of these systems and they also show that all second moment stability concepts are equivalent. In respect to S-MJLS, that represent a general case of MJLS, we present a study of stochastic stability of these continuous-time systems with infinite-time horizon. It means that we study a recent result that gives a sufficient condition for stochastic stability of this kind of system. As a contribution of this work, we introduce a study of second moment stability of a continuoustime MJLS, but now with horizon defined by a stopping time = TN associated with the accumulated N-th failure or repair periods, after which the system is brought to a halt for maintenance. Therefore, we adapt the second moment -stability concept and we present a result that gives necessary and sufficient conditions for -stability of these systems. Furthermore, we show that such conditions obtained are more restrictive than that associated with the infinite-time horizon. Finally, we also prove that all second moment -stability concepts are equivalent.